COMPARING THE EFFECTIVENESS OF YOGA AND INTERVAL TRAINING ON CARDIOVASCULAR HEALTH - Sukumar, Biju; N. R., Sangeetha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The escalating prevalence of cardiovascular diseases (CVDs) worldwide has become a significant public health concern, necessitating innovative and effective strategies for prevention and management. With the World Health Organization estimating that CVDs account for approximately 32% of all global deaths, the urgency for non-pharmacological interventions is paramount. This research paper delves into a comparative analysis of two widely practised interventions—yoga and high-intensity interval training (HIIT)—to ascertain their respective impacts on cardiovascular health. Employing a rigorous quantitative research design, we meticulously assessed a range of cardiovascular metrics, including blood pressure, heart rate variability (HRV), and lipid profiles, among a diverse cohort of adult participants engaged in an 8-week program of either yoga or HIIT. To ensure the integrity of our findings, we implemented an Analysis of Covariance (ANCOVA), effectively controlling for potential confounding variables that could skew our results. The analysis yielded compelling evidence that both interventions led to statistically significant improvements in cardiovascular health parameters; however, the results indicated that HIIT was more effective in reducing systolic blood pressure and enhancing HRV when compared to yoga. These findings underscore the necessity for healthcare professionals to consider exercise modalities like HIIT as a viable approach to the holistic management of cardiovascular health.